Influence of Habitat Characteristics on Shore‐Spawning Kokanee. Issue 6 (30th September 2014) - Whitlock, Steven L.; Quist, Michael C.; Dux, Andrew M.
Abstract: Sockeye Salmon Oncorhynchus nerka and kokanee (lacustrine Sockeye Salmon) commonly spawn in both lentic and lotic environments; however, the habitat requirements of shore spawners are virtually unknown relative to those of stream spawners. A laboratory experiment and an in situ incubation study were conducted to better understand the influence of habitat characteristics on the shoreline incubation success of kokanee. The laboratory experiment assessed kokanee intragravel survival, fry emergence, and fry condition in response to eight substrate treatments. The in situ study, conducted at three major shoreline spawning sites in Lake Pend Oreille, Idaho, evaluated the effect of depth, substrate composition, dissolved oxygen, shoreline slope, and groundwater on intragravel survival. Substrate size composition was generally a poor predictor of survival in both the laboratory experiment and in situ study; although, fry condition and counts of emerged fry in the laboratory were lowest for the substrate treatment that had the highest proportion of fine sediment. Results of the in situ study suggest that groundwater flow plays an important role in enhancing intragravel survival in habitats generally considered unsuitable for spawning. Received January 7, 2014; accepted May 28, 2014